DYNAMIC REPLICATION STRATEGY BASED ON EXPONENTIAL MODEL AND DEPENDENCY RELATIONSHIPS IN DATA GRID (Journal of Information and Communication Technology, 2012)
Data grid is an infrastructure that manages huge amounts of data files, and provides intensive computational resources across geographically distributed collaboration. In order to speed up the data access and reduce bandwidth consumption, data grid replicates essential data in multiple locations. This paper studies the data replication strategy in data grid, taking into account the exponential growth/decay of data files and the dependency relationships between them. Simulation results (via OptorSim) show that the proposed strategy outperformed existing work in the measured metrics – mean job execution time, effective network usage and average storage usage.